The effect of cow manure amendment and the ratio of gold mine tailings on sweet potato gold phytomining - Noviardi, Rhazista; Joy, Benny; Sudirja, Rija; Setiawati, Mieke Rochimi; Djuwansah, Muhamad Rachman; Karuniawan, Agung; Sofyan, Emma Trinurani; Suryatmana, Pujawati (Journal of Degraded and Mining Lands Management, 2024)
Artisanal and small-scale gold mining has commonly used the mercury amalgamation method for gold ore extraction. The processing waste or tailings often contain gold and other metals. This study examined the effects of cow manure amendment and the ratio of gold mine tailings on sweet potato     (Ipomoea batatas L.) gold phytomining. The pot experiment was conducted in the Faculty of Agriculture greenhouse at Padjadjaran University in Indonesia. The sweet potato MZ119 clone (an orange-fleshed sweet potato) was planted on a polybag (40 x 40 cm) consisting of 10 kg of planting media, which was a mixture of gold mine tailing and soil. The design used was a completely randomized design factorial with three replications. The first factor was ratios of gold mine tailing consisting of three levels, namely 30%, 50%, 70%, and 100% (w/w). The second factor was doses of organic manure, namely without cow manure, 250 g pot-1, 500 g pot-1, and 750 g pot-1. The results demonstrated that the application of cow dung and the gold mine tailings ratio (w/w) had a significant (p = 0.05) effect on plants' dry weight biomass, gold accumulation, and gold phytomining by sweet potato. The highest gold mass yield of 0.066 mg gold plant-1 was achieved by a 50% (w/w) gold mine tailing ratio and 750 g pot-1 cow manure treatment.